The Use of Role Play as a Teaching Technique to Promote Memorable Lessons in Civilisation Classrooms. The Case of Third Year English LMD Students at Laghouat University - Chorfi ,Chahrazed; Cherfaoui, Samia (Faculty of Letters and Foreign Languages Department of English, 2018)
This research aims to enhance civilisation teaching through role play. The main problem is that students find the memorisation of dates, names and historical facts too difficult. Therefore, there are many teaching strategies through which teachers can help their students to understand and recall the information easily. Since civilisation teaching is done through the lecture method only. The latter may make students feel bored and lose their interest during the session. Hence, this study shed the light on the use of strategies like role play that can actively engage students in which they learn by doing. Using role play to teach civilisation brings history to life consequently history learning can be facilitated, stored and easily retrieved. Correspondingly, this research hypothesises that the use of enhancing strategies like role play helps students to memorise civilisation courses. A descriptive and analytical study is chosen to prove or disprove this hypothesis. A questionnaire is used as method of collecting data. The data is collected from third year LMD students at English department of Amar Thelidji Laghouat University. This tool is used to look for students’ attitudes toward role play use in teaching civilisation and its impact on delivering memorable lessons. The results from the analysis of students’ questionnaire confirms the hypothesis in which students’ responses are positive toward role play use in civilisation classrooms. Thereby, this research recommends the use of teaching techniques like role play while teaching civilisation to promote memorable lessons